Evaluation of interleukins (2, 6 and 8) in immunized white rats by Salmonella enterica subspecies typhimurium and Cryptococcus neoformans antigens - AL-Samarraae, Ikram A. A. (The Iraqi Journal of Veterinary Medicine, 2018)
This study was designed to evaluate the levels of interleukins (2, 6 and 8) in immunized white rats by killed whole cell antigens of Salmonella enterica subspecies typhimurium and sonicated Cryptococcus neoformans, and using ELISA in day 10, 20, 30, 40 and 50 after immunization one hundred white rats of both sexes divided into five groups (20 rats for each). The first group was immunized by killed whole cell antigens of Salmonella enterica subspecies typhimurium (9× 108 CFU /ml) and sonicated Cryptococcus neoformans (1000 µg/ml), The second was immunized by killed whole cell antigens of Salmonella enterica subspecies typhimurium (9× 108 CFU /ml) and sonicated Cryptococcus neoformans (500 µg/ml). The third was immunized by killed whole cell antigens of Salmonella enterica subspecies typhimurium (9× 108 CFU /ml) as positive control group, The fourth was injected 1 ml of phosphate buffer saline (pH 7.2) as control negative group and fifth was immunized by sonicated antigens of Cryptococcus neoformans (1000 µg/ml). The results of IL-2 showed significant differences (P<0.05) between the 1st, 2nd and 3th groups compared with 4th and 5th group, while there was no significant difference (P≥0.05) between 4th and 5th groups. Also IL-6 showed that there were significant differences (P<0.05) between the 1st, 2nd and 3rd groups in comparison with 4th group, while there was no significant difference (P≥0.05) between the 1st, 2nd, 3rd groups and 5th group. In the IL-8 showed that there was a significant difference (P<0.01) between the1st and 2nd groups and between 3rd group and 1st and 2nd groups without significant difference (P≥0.05), also between the 1st, 2nd and 3rd groups and 4th group significant difference (P<0.05) and with a significant difference (P<0.01) between 5th group and all other groups (1st, 2nd, 3rd and 4th).